Impact of Structural OD Interventions on Organizational Performance in Pakistan: A Mixed Methods Explanatory Sequential Research Approach (Journal of Asian Development Studies, 2024)
This mixed methods explanatory sequential research study investigated the impact of structural OD interventions on organizational performance. We used a stratified random probability technique for a quantitative analysis to select 800 firms from those listed with the Securities and Exchange Commission of Pakistan (SECP). We employed SPSS to conduct the regression analysis and calculated values of regression coefficient β, t-statistic, and p-values, adjusted R2 and F-statistic. We conducted the mediation analysis and Sobel and Goodman tests to confirm the mediation among variables. The confirmatory factor analysis (CFA) is conducted to tests how the measured variables represent the number of constructs. We conducted a focus group of ten OD experts to collect the qualitative data, conduct thematic analysis, and extracted useful themes. We merged the quantitative and qualitative findings. The study concluded that structural OD interventions are strategically important for organizational performance and employee development. The findings encouraged the corporate planners to create OD interventions that are both effective and perform strongly.